The influence of Extraversion, Agreeableness, Conscientiousness, Neuroticism, Openness to Experience, Optimism, Financial Attitude, Financial Knowledge, and Financial Self-Efficacy on The Financial Behaviour of University Students in Indonesia - Rocky Rocky; Shania Nadine Kartawijaya (iBuss Management, 2021)
The advancement of e-commerce, capital markets, and financial products and services in Indonesia may give incentives for people to spend more. Thus, this may also bring unfavourable economic situations for those who do not have good financial behaviour. Therefore, it is important to know how to have good financial behaviour by knowing what are the factors that influence it. Thesubject for this research is the university students in Indonesia because the number of young investors, especially university students, in Indonesia is growing rapidly. Past studies have suggested that factors that may affect the financial behaviour of university students include: extraversion, agreeableness, conscientiousness, neuroticism, openness to experience, optimism, financial attitude, financial knowledge, and financial self-efficacy. Therefore, this research aims to know whether those nine factors influence the financial behaviour of university students in Indonesia or not. The data was gathered by distributing questionnaires to 129 respondents who are currently university students in Indonesia. The data is analysed using multiple linear regression. The findings suggest that conscientiousness, financial attitude, and financial self-efficacy has a significant influence on financial behaviour. However, extraversion, agreeableness, neuroticism, openness to experience, optimism, and financial knowledge has no significant influence on financial behaviour.Keywords:Financial Behaviour, Extraversion, Agreeableness, Conscientiousness, Neuroticism, Openness to Experience, Optimism, Financial Attitude, Financial Self-Efficacy, Financial Knowledge.